Effects of binding partners on thermal reversion rates of photoswitchable molecules - P. Maximilian M. Reed; Jaewan Jang; Ryan M. Woloschuk; Jakeb Reis; Jacques I. C. Hille; Maruti Uppalapati; G. Andrew Woolley (Proceedings of the National Academy of Sciences, 2025)
The binding of photoswitchable molecules to partners forms the basis of many naturally occurring light-dependent signaling pathways and various photopharmacological and optogenetic tools. A critical parameter affecting the function of these molecules is the thermal half-life of the light state. Reports in the literature indicate that, in some cases, a binding partner can significantly influence the thermal half-life, while in other cases it has no effect. Here, we present a unifying framework for quantitatively analyzing the effects of binding partners on thermal reversion rates. We focus on photoswitchable protein/binder interactions involving LOV domains, photoactive yellow protein, and CBCR GAF domains with partners that bind either the light or the dark state of the photoswitchable domain. We show that the effect of a binding partner depends on the extent to which the transition state for reversion resembles the dark state or the light state. We quantify this resemblance with a ϕ switching value, where ϕ switching = 1 if the conformation of the part of the photoswitchable molecule that interacts with the binding partner closely resembles its dark state conformation and ϕ switching = 0 if it resembles its light state. In addition to providing information on the transition state for switching, this analysis can guide the design of photoswitchable systems that retain useful thermal half-lives in practice. The analysis also provides a basis for the use of simple kinetic measurements to determine effective changes in affinity even in complex milieu.